Computer-aided design and computer-aided manufacturing indirect versus direct composite restorations: A randomized clinical trial - Rocha Gomes Torres, Carlos [UNESP]; Caroline Moreira Andrade, Adrielle [UNESP]; Valente Pinho Mafetano, Ana Paula [UNESP]; Stabile de Abreu, Fabrícia [UNESP]; de Souza Andrade, Danilo [UNESP]; Cintra Mailart, Mariane [UNESP]; Aun de Barros Lima Rocha Campello de Souza, Maria Luíza [UNESP]; Guimarães Alarça Nunes, Lilian [UNESP]; Ariel Rodrigues de Araújo, Carlos [UNESP]; Di Nicoló, Rebeca [UNESP]; Bühler Borges, Alessandra [UNESP] (Wiley, 2021)
Objective: This study compared the clinical performance of large indirect restorations (IRs) versus direct restorations (DRs) in posterior teeth. Methods: Thirty subjects received two class II restorations (n = 60), one fabricated from a precured composite block (Grandio Blocs, VOCO) for the indirect technique (IT) and the other with light-cured composite (GrandioSO, VOCO) for the direct technique (DT). For IT, the restoration was created using the computer-aided design and computer-aided manufacturer (CAD/CAM) system. For DT, the material was applied light-cured by using a layering technique. All restorations were evaluated by using the World Dental Federation criteria. Results: Twenty-three subjects attended the 2-year recall, and 46 restorations were evaluated. No significant differences were detected between the techniques for most parameters analyzed (p > 0.05). For “color match” at 7 days and 6 months, better results were observed for the DT. In relation to the overall scores, all restorations were esthetically acceptable after 2 years, while 93.3% of DT and 90% of IT showed acceptable function. For biological scores, 96.67% of DRs and 100% of IRs was acceptable after 24 months. Considering all properties, the success rates were 93.3% for DRs and 90% for IRs. Conclusions: After 2 years, both restorations presented similar and good clinical behavior for all the properties analyzed. Clinical significance: Light-cured direct posterior composite restorations may perform similarly to indirect composite restorations made with precured CAD/CAM composite blocks up to 2 years.
Keywords: CAD/CAM; clinical trial; composite; indirect restoration